Red string theory : a novel - Jessen, Lauren Kung (Forever, 2024)
"Just a date . . . or a twist of fate? When it comes to love and art, Rooney Gao believes in signs. Most of all, she believes in the Chinese legend that everyone is tied to their one true love by the red string of fate. And that belief has inspired her career as an artist, as well as the large art installations she makes with (obviously) red string. That is until artist's block strikes and Rooney begins to question everything. But then fate leads her to the perfect guy . . . Jack Liu is perfect. He's absurdly smart, successful, handsome, and after one enchanting New York night--under icy February skies and fueled by fried dumplings--all signs point to destiny. Only Jack doesn't believe. And after their magical date, it looks like they might be lost to each other forever . . . until they're given one more chance to reconnect. But can Rooney convince a reluctant skeptic to take a leap of fate?"--